Defoliation severity is positively related to soil solution nitrogen availability and negatively related to soil nitrogen concentrations following a multi-year invasive insect irruption. Issue 6 (13th November 2020) - Conrad-Rooney, Emma; Barker Plotkin, Audrey; Pasquarella, Valerie J; Elkinton, Joseph; Chandler, Jennifer L; Matthes, Jaclyn Hatala
Abstract: Understanding connections between ecosystem nitrogen (N) cycling and invasive insect defoliation could facilitate the prediction of disturbance impacts across a range of spatial scales. In this study we investigated relationships between ecosystem N cycling and tree defoliation during a recent 2015–18 irruption of invasive gypsy moth caterpillars ( Lymantria dispar ), which can cause tree stress and sometimes mortality following multiple years of defoliation. Nitrogen is a critical nutrient that limits the growth of caterpillars and plants in temperate forests. In this study, we assessed the associations among N concentrations, soil solution N availability and defoliation intensity by L. dispar at the scale of individual trees and forest plots. We measured leaf and soil N concentrations and soil solution inorganic N availability among individual red oak trees ( Quercus rubra ) in Amherst, MA and across a network of forest plots in Central Massachusetts. We combined these field data with estimated defoliation severity derived from Landsat imagery to assess relationships between plot-scale defoliation and ecosystem N cycling. We found that trees in soil with lower N concentrations experienced more herbivory than trees in soil with higher N concentrations. Additionally, forest plots with lower N soil were correlated with more severe L. dispar defoliation, which matched the tree-level relationship. The amount of inorganic N in soil solution was strongly positively correlated with defoliation intensity and the number of sequential years of defoliation. These results suggested that higher ecosystem N pools might promote the resistance of oak trees to L. dispar defoliation and that defoliation severity across multiple years is associated with a linear increase in soil solution inorganic N. Abstract : A severe, multi-year gypsy moth population irruption occurred in a temperate New England forest that caused intense leaf herbivory and tree defoliation. We found that trees and forest stands with lower soil nitrogen concentrations experienced more defoliation than those with higher soil nitrogen concentrations. The inorganic nitrogen in soil solution was strongly positively correlated with defoliation intensity and the number of sequential years of defoliation. This could suggest that higher nitrogen pools might promote the resistance of oak trees to defoliation and that defoliation severity across multiple years is associated with a linear increase in soil solution inorganic nitrogen.